Analisis Media Pembelajaran BK dengan Menggunakan Media Pohon Karir di SMP Negeri 1 Percut Sei Tuan - Bancin, Wahdaniati; Rahman, Muhammad Yandi; Murni, Sheila Natasya; Fadilah, Annisa Nurul; Saragih, Bunaisah; Febriani, Melisa; Muliani, Amelia Sri (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research aims to provide solutions for Percut Sei Tuan 1 Public Middle School students in facing the career planning problems they are experiencing, and also aims to identify the various causes of these career planning problems. This research uses a qualitative research method with a descriptive qualitative approach. Data collection techniques use observation, interviews and documentation. The research subjects were students of SMP Negeri 1 Percut Sei Tuan. The results of this research show that several students at SMP Negeri 1 Percut Sei Tuan experienced difficulties in career planning. The causes of the difficulties they experience in choosing a career also vary.